Analysis Of Financial Performance Budget Realization Bogor Regional Revenue And Expenditures (APBD). Period 2016-2021 - Novita Sari, Diana; Sundarta, M. Imam; A. Syukur, Dudung; Faizal, Harun (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2022)
This study aims to determine the financial performance of the realization of the Regional Revenue and Expenditure Budget managed by the regional government of Bogor City for the 2016-2021 period. The method used in this research is descriptive qualitative. Thus, an analysis of financial performance is carried out using measuring instruments in the form of regional financial ratios such as efficiency ratios, effectiveness ratios, independence ratios, harmony ratios, and growth ratios. The results of this study indicate that the average efficiency ratio is still below 100% which is categorized as less efficient, the effectiveness ratio is said to be very effective in realizing regional original income with an average of above 100%, and the ratio of regional financial independence is moderate with a participatory pattern, the compatibility ratio is not yet said to be optimal because the Bogor City government still prioritizes most of its funds for operating expenditures compared to capital expenditures which are quite low, the ratio of growth of regional original income is positive compared to regional revenues and capital expenditures are still relatively low compared to operating expenditures which are quite high.